Inversión privada, gasto público y presión tributaria en América Latina - Luis Felipe Brito-Gaona; Emma Iglesias (Estudios de Economía, 2017)
– This paper looks for empirical evidence to show if a very interventionist government stimulates or not private investment in Latin America. Using the same model as Caballero-Urdiales y López-Gallardo (2012), we extend their analysis from five Latin-American countries to all Latin America. The results from our estimated elasticities show evidence in support of three hypothesis: (1) that tax burden (taxes on income and consumption) has significant effects on privateinvestment; (2) that public investment has a crowding out effect with private investment; (3) and that in order to stimulate private investment, the government should have very little intervention.
Keywords: F21; H24; H25; H54; 330; Private investment; gross domestic produc; public investment; income tax; value added tax